Idebenone and reduced cardiac hypertrophy in Friedreich's ataxia. Issue 4 (1st April 2002) - Hausse, A O; Aggoun, Y; Bonnet, D; Sidi, D; Munnich, A; Rötig, A; Rustin, P
Abstract : Background: Friedreich's ataxia encodes a protein of unknown function, frataxin. The loss of frataxin is caused by a large GAA trinucleotide expansion in the first intron of the gene, resulting in deficiency of a Krebs cycle enzyme, aconitase, and of three mitochondrial respiratory chain complexes (I–III). This causes oxidative stress. Idebenone, a short chain quinone acting as an antioxidant, has been shown to protect heart muscle against oxidative stress in some patients. Objective: To assess the efficiency of idebenone on cardiac hypertrophy in Friedreich's ataxia. Design: Prospective, open trial. Setting: Tertiary care centre. Methods: Idebenone (5 mg/kg/day) was given orally to 38 patients with Friedreich's ataxia aged 4–22 years (20 males, 18 females). Cardiac ultrasound indices were recorded before and after idebenone treatment. Results: After six months, cardiac ultrasound indicated a reduction in left ventricular mass of more than 20% in about half the patients (p < 0.001). The shortening fraction was initially reduced in six of the 38 patients (by between 11–26%) and it improved in five of these. In one patient, the shortening fraction only responded to 10 mg/kg/day of idebenone. No correlation was found between responsiveness to idebenone and age, sex, initial ultrasound indices, or the number of GAA repeats in the frataxin gene. Conclusions: Idebenone is effective at controlling cardiac hypertrophy in Friedreich's ataxia. As the drug has no serious side effects, there is a good case for giving it continuously in a dose of 5–10 mg/kg/day in patients with Friedreich's ataxia at the onset of hypertrophic cardiomyopathy.